Third Year Winner: Saving their Indian ’Sisters’: British Women’s Activism in the late 19th Century: HIST 3420, The British Empire from 1600 to the Present. CD: Colin McMahon. - Silva, Karen (Noteworthy: The LA&PS Writing Prizes, 2017)
“Saving their Indian ‘Sisters’: British Women’s Activism in India in the Late Nineteenth Century” is certainly a most worthy winner of the third-year Faculty essay prize. In her compelling and delightfully written history, author Karen Silva analyses the methods used and reasons why these women activists sought to lift up the lives of the women in the Indian colony, and in doing so seeks to demonstrate that the Empire was not solely a male enterprise. She also clearly exposes the fact that these efforts, while usually motivated by a deep concern, often did as much harm as good. The resulting essay most ably integrates the author’s extensive research from a wide variety of sources into a well told narrative which is indeed enlightening and a great pleasure to read. It is a piece of writing of which the author should be most proud.